Influence of Application of Blended Learning Models with Video Conferences Media on Students' Mathematical Communication Skills - Tia Utami; Hendri Handoko (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2023)
Students' mathematical communication skills are an important element so that students are able to construct their own abilities in mathematics learning. In order for mathematical learning goals to be achieved, teachers must be able to create effective and efficient mathematical learning with the right learning model to be able to provide opportunities and encourage students to practice their mathematical communication skills. The purpose of this research is to find out the influence of the application of blended learning models with conferennces video media on students' mathematical communication skills. This learning model was tested on cirebon veteran vocational school students using experimental classes, namely grade 12 AKL as many as 20 students with a pre-test-post-test one group design. Data collection techniques in this study through tests and questionnaires. The data analysis techniques used are the T-Test paired sample test, the N-Gain test and the simple linear regression equation test with the help of SPSS. The results of this study showed an improvement in students' mathematical communication skills after the application of blended learning models with video conferences and there was a significant positive influence